2014
DOI: 10.1111/cei.12228
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte implication in renal allograft dysfunction

Abstract: SummaryMacrophages are involved in the development and progression of kidney fibrosis. The aim of this study was to analyse the phenotype of circulating monocytes and their ability to predict kidney allograft dysfunction in living kidney transplant recipients. Whole blood samples from 25 kidney recipients and 17 donors were collected at five time-points. Monocyte phenotype was analysed by flow cytometry, and interleukin (IL)-10 and soluble CD163 by enzyme-linked immunosorbent assay. One week after transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…21 Increasing evidence shows that intragraft macrophages, particularly activated macrophages, correlate with a poor outcome in renal transplantation in humans and animal models. [22][23][24][25][26][27][28][29] In addition, a-SMA + myofibroblast accumulation has been recognized as an early marker of chronic renal allograft dysfunction. 30,31 Of note, CD68 + macrophages and a-SMA + myofibroblasts colocalize in areas of active interstitial fibrosis in renal allografts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Increasing evidence shows that intragraft macrophages, particularly activated macrophages, correlate with a poor outcome in renal transplantation in humans and animal models. [22][23][24][25][26][27][28][29] In addition, a-SMA + myofibroblast accumulation has been recognized as an early marker of chronic renal allograft dysfunction. 30,31 Of note, CD68 + macrophages and a-SMA + myofibroblasts colocalize in areas of active interstitial fibrosis in renal allografts.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Of note, CD68 + macrophages and a-SMA + myofibroblasts colocalize in areas of active interstitial fibrosis in renal allografts. 25,27,29 Although macrophages may stimulate renal fibrosis in an indirect fashion by producing proinflammatory and profibrotic cytokines and growth factors, 13 a direct link between inflammatory macrophages and myofibroblast accumulation during chronic allograft rejection has remained undefined. In this study, we confirmed that intragraft CD68 + macrophages correlated with loss of allograft function and the development of interstitial fibrosis in patients with chronic active allograft rejection, consistent with previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group showed that circulating monocytes could be useful as a prognostic tool with respect to graft dysfunction in living kidney recipients . In this work, we focus on gene expression of inflammatory and fibrotic markers and macrophage infiltration in kidneys from DDs and LDs at the time of transplantation and after 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in solid organ transplantation suggest that NK cells are paradoxically involved in both graft acceptance and dysfunction, through their influence on the immune pathways of allograft tolerance and rejection, respectively [8][9][10] . Meanwhile, it is suggested that it could be useful to analyze CD163 by flow cytometry and enzyme-linked immunosorbent assay in the prediction of renal graft function after transplantation [11] . However, little is known about the exact mechanisms by which CD56+ or CD163+ cells contribute to the rejection or acceptance of kidney allografts.…”
mentioning
confidence: 99%